Reactivity of the human hemoglobin "Dark side"1. Issue 2 (3rd January 2013) - Ascenzi, Paolo; Leboffe, Loris; Polticelli, Fabio
Abstract Summary: Ligand binding to the heme distal side is a paradigm of biochemistry. However, X‐ray crystallographic studies highlighted the possibility that O2 and NO2− may bind to the proximal heme side of ferrous human hemoglobin (Hb) α‐chains complexed with the α‐hemoglobin stabilizing protein and to ferric human hemoglobin β‐chains, respectively. Strikingly, the role generally played by the proximal HisF8 residue is played by the distal HisE7 side chain forming the trans axial ligand of the heme–Fe atom. This: i) brings to light that Hb may utilize both heme distal and proximal sides for ligand discrimination, ii) draws attention to the nonequivalence of α‐ and β‐chains, and iii) highlights the possibility that partially unfolded Hb derivatives may display transient ligand‐binding properties different from those of the native globin. © 2013 IUBMB Life, 65(2)121–126, 2013